The Two-Step Australian Immigration Policy and its Impact on Immigrant Employment Outcomes - Robert G. Gregory (Institute for the Study of Labor (IZA), 2014)
Three decades ago most immigrants to Australia with work entitlements came as permanent settlers. Today the annual allocation of temporary visas, with work entitlements, outnumbers permanent settler visas by a ratio of three to one. The new environment, with so many temporary visa holders, has led to a two-step immigration policy whereby an increasing proportion of immigrants come first as a temporary immigrant, to work or study, and then seek to move to permanent status. Around one half of permanent visas are allocated on-shore to those who hold temporary visas with work rights. The labour market implications of this new two-step system are substantial. Immigrants from non-English speaking countries (NES), are affected most. In their early years in Australia, they have substantially reduced full-time employment and substantially increased part-time employment, usually while attending an education institution. Three years after arrival one third of NES immigrants are now employed part-time which, rather than unemployment, is becoming their principal pathway to full-time labour market integration. Surprisingly, little has changed for immigrants from English speaking countries (ES).
Keywords: J15; J61; J68; F22; 330; immigrant part-time employment; fee paying foreign students; temporary employment visas; labour market integration; immigrants; employment